(untitled) (Journal of the College of Basic Education, 2022)
Fabric design is an art that has rules, origins, and laws directly related to the individual that deserve care and attention, and it is no less important than all other fine arts. Curtain fabric designs are clearly subject and affected by the social and economic environment and the development taking place in the technical field, which formed motives that gave the designer the ability to devise and innovate systems. New relationships resulting from his self-sensitivity to the components from which he derives the design idea as well as his own cultural and philosophical level, which are reliable ingredients and motives in fabric designs.